SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN KREDIT Di CREDIT UNION “PARDIS” DENGAN METODE FUZZY MAMDANI - Ertina Sabarita Barus; Hesalorafika Ginting (UPPM, 2017)
Credit is a loan by another party that will be returned at a certain time. In conducting credit analysis, if done properly can run as the first screening for the company to avoid bad credit, in the process of data processing candidate This creditor will appear vague variables that must be addressed by credit analyst.Credit Union